2019
DOI: 10.4085/1062-6050-93-18
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Activity Levels After Sport-Related Concussion Using Actigraph and Mobile (mHealth) Technologies

Abstract: Context Interest in identifying the effects of physical and mental activity on recovery after sport-related concussion is growing. Clinical studies of concussed athletes' activities require well-validated methods for tracking their intensity and timing. Objective To develop and validate a novel multimodal approach to monitoring activity postconcussion using mobile (mHealth) technologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…A time period of two weeks was selected as the participants were most compliant in wearing the device in the first two weeks after the initial assessment. Additionally, this time period is consistent with another study in a similar population [ 23 ]. We then used a Receiver Operating Characteristic (ROC) and Area under the Curve (AUC) analysis to identify different cutpoint thresholds to distinguish between groups for each exercise/activity variable.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…A time period of two weeks was selected as the participants were most compliant in wearing the device in the first two weeks after the initial assessment. Additionally, this time period is consistent with another study in a similar population [ 23 ]. We then used a Receiver Operating Characteristic (ROC) and Area under the Curve (AUC) analysis to identify different cutpoint thresholds to distinguish between groups for each exercise/activity variable.…”
Section: Methodssupporting
confidence: 92%
“…The median step count per day over the two-week period was 10,893 for those who received clearance <28 days and 7571 for those who took ≥28 days to receive RTP clearance. Interestingly, the values obtained for those who took ≥28 days to receive RTP clearance are similar to a past study, where researchers observed an average count of approximately 6600 steps/day in the days following a concussion [23]. Furthermore, a systematic review reported normative values among boys and girls to range on average 12,000 to 16,000 steps/day and 10,000 to 13,000 steps/day, respectively [25].…”
Section: Discussionsupporting
confidence: 84%
“…For this sleep-monitoring sub-study, participants were given a commercially available actigraph (CA) and a mobile application developed for the purpose of this study. 13 Previous literature has reported high concordance between data recorded by the Fitbit Charge HR and clinical actigraphs in young adults and adolescents. 14,15 The general methodology for this study and the mobile application development has also been described (focused on physical activity metrics) in a prior publication.…”
Section: Subjectsmentioning
confidence: 79%
“…14,15 The general methodology for this study and the mobile application development has also been described (focused on physical activity metrics) in a prior publication. 13 Participants were asked to wear the actigraph as often as possible (day and night) for 2 weeks to provide daily sleep and activity metrics. The mobile survey (MS), delivered nightly, asked about total amount of sleep and total time spent in bed the night before.…”
Section: Subjectsmentioning
confidence: 99%
“…The motor activity corresponds to a weighting voltage collected with an actigraph watch (Actiwatch, Cambridge Neurotechnology Ltd., England, model AW4) located in the right wrist, which records movements over 0.5g in a sampling frequency of 32 Hz. Some advantages of actigraphs accelerometers is that they are inexpensive and well-known activity trackers [19] and, in addition, they are easy to wear and allow collecting data from day and night [20].…”
Section: Dataset Descriptionmentioning
confidence: 99%